2007
DOI: 10.2319/0003-3219(2007)077[0404:osoipw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Space Opening in Patients with Congenitally Missing Lateral Incisors

Abstract: To avoid a high degree of alveolar bone atrophy and the risk of relapse and retreatment, orthodontic treatment involving tooth movement should not be initiated before the age of 13 years. Furthermore, it is important to maintain anchorage of the upper incisors because high incisor proclination causes extra-axial stress on the implant. An interdisciplinary approach is essential to provide the best treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…Previously published studies are indeed inconclusive; reports showing a significantly reduced ridge dimension (Beyer et al. ; Uribe et al. ,b) as well as reports showing stable ridge dimensions on the long term (Spear et al.…”
Section: Discussionmentioning
confidence: 98%
“…Previously published studies are indeed inconclusive; reports showing a significantly reduced ridge dimension (Beyer et al. ; Uribe et al. ,b) as well as reports showing stable ridge dimensions on the long term (Spear et al.…”
Section: Discussionmentioning
confidence: 98%
“…indicate that new bone also showed resorption after the orthodontic treatment and before implantation and advised to postpone the orthodontic treatment until the patient is old enough for implantation. [16] However, other authors claimed that the new bone is stable over long term[613] and age of the patient is not a crucial factor in the decision of treatment time. In the present case, the lateral tooth was moved to midline to form new bone in extraction space.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of treatment are described for congenital agenesis of the LI: space closure with mesial repositioning of the canine, followed by tooth recontouring; or space opening followed by the placement of a prosthesis, transplant, or dental implant 27. The knowledge regarding craniofacial growth and detailed orthodontic treatment is fundamental as it assists correct teeth positioning in both types of treatment and helps to improve the volume of the alveolar ridge for the implant placement 28,29. Several studies have assessed these two treatment options,3032 and others revealed the opinion of dentists and laypersons concerning smile attractiveness 12,23.…”
Section: Discussionmentioning
confidence: 99%